Is It Attachment Style or Socio-Demography: Singlehood in a Representative Sample - Petrowski, Katja; Schurig, Susan; Schmutzer, Gabriele; Brähler, Elmar; Stöbel-Richter, Yve (Frontiers in Psychology, 2015)
Since the percentage of single adults is steadily increasing, the reasons for this development have become a matter of growing interest. Hereby, an individual’s attachment style may have a connection to the partnership status. In the following analysis, attachment style, gender, age, education, and income were compared in regard to the partnership status. Furthermore, an analysis of variance was computed to compare the attachment style within different groups. In 2012, a sample of 1,676 representative participants was used. The participants were aged 18 to 60 (M = 41.0, SD = 12.3); 54% of the sample were female, and 40% were single. Attachment-related attitudes were assessed with the German version of the adult attachment scale (AAS). Single adult males did not show a more anxious attachment style than single adult females or females in relationships. Younger, i.e., 18 to 30 years old, paired individuals showed greater attachment anxiety than single individuals, whereby single individuals between the ages of 31 to 45 showed greater attachment anxiety than individuals in relationships. In addition, single individuals more frequently had obtained their high school diploma in contrast to individuals in relationships. Concerning attachment style, the individuals who had not completed their high school diploma showed less faith in others independent of singlehood or being in a relationship. Concerning age, older single individuals, i.e., 46 to 60 years, felt less comfortable in respect to closeness and showed less faith in others compared to paired individuals. Logistic regression showed that individuals were not single if they did not mind depending on others, showed high attachment anxiety, were older, and had lower education. An income below € 2000/month was linked to a nearly 13-fold increase of likelihood of being single. In sum, the attachment style had a differential age-dependent association to singlehood versus being in a relationship. Education played also a role, exclusively concerning faith in others.